The examination of the common agricultural policy of the European Community and the Turkish agricultural policy and some preliminary reviews on Turkish agricultural harmonization - Mutaf, Erdem (My University, 1989)
unknown
Keywords: Avrupa Birliği_Tarım Politikası; Avrupa Birliği_Tarım_Türkiye